P-85 Thrombolysis for pulmonary embolism in palliative care: a case report. (1st March 2017) - Macfarlane, Mike; Gilhooley, Louise; Griffiths, Tina; Frost, Stephen; Willis, Derek
Abstract : Background: Thrombolysis for pulmonary embolism (PE) in a patient with advanced cancer has never been reported in the literature. Whilst not an absolute contraindication, most clinicians would be wary of thrombolysing a patient with a limited life expectancy. A case is presented of a patient with advanced mesothelioma who received thrombolysis treatment with a resultant significant improvement in pleuritic chest pain and dyspnoea. History: The patient was a 69 year old man who was diagnosed with epithelioid mesothelioma and received radiotherapy to his right chest followed by palliative chemotherapy. Subsequent CT scanning showed disease progression and the patient declined further chemotherapy. Thrombolysis: The patient was admitted to hospital with sudden-onset shortness of breath and right sided chest discomfort which was felt to be due to disease progression. Three days later the patient developed new, severe left sided pleuritic chest pain and acute breathlessness. The patient was thrombolysed with alteplase (50 mg IV over 1 hour) on clinical suspicion of a PE. The pleuritic chest pain resolved completely and the acute severe dyspnoea improved significantly within two hours of treatment and a CTPA later confirmed acute-on-chronic pulmonary thromboembolism as well as progressive mesothelioma. The patient was transferred to the hospice four days later for ongoing management and end-of-life care. Effect of Thrombolysis on Symptom Control On admission to the hospice, the patient contined to complain of mild to moderate dyspnoea but had no pain. He was commenced on regular immediate-release morphine (10 mg QDS) for breathlessness but only required one breakthrough dose of analgesia before his condition deteriorated. The patient died comfortably nine days after thrombolysis treatment. Conclusion: Thrombolysis was very effective in controlling pleuritic chest pain and acute severe dyspnoea in this patient with PE and advanced cancer with a limited life expectancy.